On this page, we can see all the rules for parentheses in one spot. Rule Parentheses (a + b) (c + d) = a ⋅ c + a ⋅ d + b ⋅ c + b ⋅ d a + (c + d) = a + c + d a −(c + d) = a − c − d a ⋅(b + c) = a ⋅ b + a ⋅ c (a + b) (c + d) = a ⋅ c + a ⋅ d + b ⋅ c + b ⋅ d a + (c + d) = a + c + d a −(c + d) = a − c − d a ⋅(b + c) = a ⋅ b + a ⋅ c Note! Remember to write the terms in descending order! Then it will look like this: 2x3 − 4x2 + 5x − 3 2x3 − 4x2 + 5x − 3 Example 1 Evaluate x + (−2x + 5) x + (−2x + 5) = x − 2x + 5 = −x + 5 Example 2 Evaluate 4 −(12 − 3x2) 4 −(12 − 3x2) = 4 − 12 + 3x2 = 3x2 − 8 Example 3 Evaluate −4x2 (2 − x) − 4x2 (2 − x) = −8x2 + 4x3 = 4x3 − 8x2 Example 4 Evaluate (x + 1) (x − 2) = (x + 1) (x − 2) = x2 − 2x + x − 2 = x2 − x − 2 (x + 1) (x − 2) = x2 − 2x + x − 2 = x2 − x − 2 Example 5 Evaluate (3x2 + y) (2 − x) = (3x2 + y) (2 − x) = 6x2 − 3x3 + 2y − xy = −3x3 + 6x2 − xy + 2y (3x2 + y) (2 − x) = 6x2 − 3x3 + 2y − xy = −3x3 + 6x2 − xy + 2y Example 6 Evaluate (2x + 3) (4x − 5) = (2x + 3) (4x − 5) = 2x ⋅ 4x + 2x ⋅(−5) + 3 ⋅ 4x + 3 ⋅(−5) = 8x2 + (−10x) + 12x − 15 = 8x2 + 2x − 15 (2x + 3) (4x − 5) = 2x ⋅ 4x + 2x ⋅(−5) + 3 ⋅ 4x + 3 ⋅(−5) = 8x2 + (−10x) + 12x − 15 = 8x2 + 2x − 15